Influence of decrease in the muscle activity during mastication on occurrence of the Stage II transport. Issue 2 (April 2019) - Komine, Akiko; Ishida, Ryo; Yamashita, Shuichiro
Abstract: Purpose: The purpose of this study was to examine the hypothesis that in the process from food ingestion to swallowing, intentional decrease in the muscle activity during mastication would affect the number of chewing strokes, and thus the occurrence of Stage II transport (St2Tr) or the number of swallowing. Methods: Twenty adults with healthy dentition were instructed to make (1) normal mastication and (2) mastication with 50% muscle activity (50% mastication), controlled by visual feedback with electromyogram. Gummy jelly was selected as a test food. The oropharynx was observed during the sequence of events from the start of mastication until swallowing using a nasal endoscope. The number of chewing strokes was calculated by rhythmical masseter muscle activity on electromyogram. Results: The number of chewing strokes increased with 50% mastication. There was a particularly noticeable increase in the number of pre-St2Tr strokes. No effect on the number of additional swallows was seen as a result of 50% mastication. Conclusions: The present study supported the hypothesis that intentional decrease in the muscle activity during mastication affected the number of chewing strokes and the occurrence of St2Tr. Particularly, this tendency was noticeable during the mastication before the start of St2Tr. However, our results did not support a question as to the number of swallowing.